Formulation, Characteristics and Viability Probiotics Cell of Biscuit Production from Hotong Flour (Setaria italica (L) Beauv.), Walnut (Canarium indicum L.), Enriched by Probiotic Cream - Wattilete, Jeirel; Fibri, Dwi Larasatie Nur; Rahayu, Endang Sutriswati (agriTECH, 2025)
Hotong (Setaria italica (L) Beauv.) and walnut (Canarium indicum L.) are nutrient-rich local foods from Maluku Province, Indonesia, significant health. In this context, biscuit enriched with probiotic cream are a recommended snack for enhancing nutrition and promoting balance of the intestinal microflora, at a sufficient quantity of 107 log CFU/g. Therefore, this study aimed to objectively evaluate the physicochemical and organoleptic characteristics of biscuit, as well as assess probiotic viability. The used was a completely randomized design (CRD) with three different formulation treatments containing hotong flour and walnut at ratios of 40%:10% (F1), 35%:15% (F2), and 30%:20% (F3). Probiotic cell viability was analyzed at temperatures of 20 °C, 37 °C, and 45 °C. The results showed that F3 had the most favorable formulation regarding nutritional adequacy rate with 173 kcal energy, 10% fat,  4.41% protein, 5.20% carbohydrate, and 2 g sugar. It featured a crisp texture and increasingly darker colors, in line with the outcomes of sensory evaluations. F3 was the preferred, achieving high scores for color (5.38), taste (6.13), aroma (5.13), breakability (5.86), crispness (6), aftertaste (5.02), and overall quality (6.03). Cell viability for all treatments was higher at 20 °C and remained above 107 log CFU/g.